Preparation method of graphene oxide loaded nanoparticle functional anticorrosive coating

By using composite materials with graphene oxide-loaded nanoparticles in the coating, the problems of graphene oxide agglomeration and coating structural defects are solved, and the protective performance and diversification of the coating are significantly improved.

CN119775865APending Publication Date: 2025-04-08GUANGXI UNIV

Patent Information

Application Number
CN202510090626.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Graphene oxide is prone to agglomeration in the coating, resulting in a decrease in the anticorrosion performance of the coating, and micropores and microcracks may appear during the preparation process, further reducing the anticorrosion performance.

Method used

A functional anticorrosion coating is prepared by using graphene oxide-laden nanoparticles as filler. Nanoparticles improve the structure of the coating, fill micropores and microcracks, and enhance the density of the coating.

Benefits of technology

The dispersion and stability of graphene oxide in the coating is significantly improved, the protective performance of the coating is enhanced, and the wear resistance, impact resistance and ultraviolet resistance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775865A_ABST
    Figure CN119775865A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a graphene oxide loaded nanoparticle functional anticorrosive coating. The preparation method comprises the following steps: (1) preparing a graphene oxide loaded nanoparticle composite material; and (2) preparing the anticorrosive coating, namely weighing dimethylbenzene, n-butyl alcohol and filler according to a ratio, performing ultrasonic treatment, weighing epoxy resin, continuously performing ultrasonic treatment and stirring, dropwise adding a defoaming agent, a flatting agent, a wetting dispersant and a curing agent, stirring, standing, and spraying on the surface of a matrix to serve as the anticorrosive coating. According to the anticorrosive filler prepared by the preparation method, the problem that graphene oxide agglomerates in a coating is solved, nano-particles are introduced to optimize a coating structure, micropores and microcracks in the coating are filled, the compactness of the coating is enhanced, defects in the coating are reduced, and the protective performance of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and particularly relates to a method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating. Background Art

[0002] With the vigorous development of the marine economy and the continuous advancement of marine engineering construction, the demand for marine anti-corrosion coatings is also growing. In marine engineering fields such as offshore facilities, coastal and bay structures, offshore platforms, mooring systems, submarine pipelines, and various marine resource equipment and engineering buildings, anti-corrosion coatings are required to protect their metal structures from corrosion. This has promoted the rapid development of the marine anti-corrosion coating industry, and at the same time has put forward higher requirements on the performance of coatings.

[0003] Graphene is a two-dimensional hexagonal honeycomb lattice carbon nanomaterial composed of carbon atoms arranged strictly in a hexagonal pattern. It has unique physical and chemical properties that are beneficial to the development of anti-corrosion coatings. As an oxide of graphene, graphene oxide contains abundant oxygen-containing functional groups (such as hydroxyl groups, carboxyl groups, etc.) on its surface. These functional groups make graphene oxide easy to be covalently and non-covalently modified, thus giving it a wider range of application possibilities. In addition, graphene oxide has excellent physical barrier capabilities and can form a dense barrier in the coating to effectively block the penetration of corrosive media. These characteristics make graphene oxide a potential high-quality material in the field of anti-corrosion coatings.

[0004] The dispersibility and stability of graphene oxide in anti-corrosion coatings are the key to its application. Due to its nanoscale size and unique flaky structure, graphene oxide has strong van der Waals forces and π-π interactions. These characteristics make it easy to agglomerate in the coating system, thereby weakening the overall anti-corrosion performance of the coating. In addition, in the coating preparation process, solvent volatilization and improper curing process may cause defects such as micropores and microcracks in the coating using graphene oxide alone. These defects provide a shortcut for the corrosive medium to penetrate, further reducing the anti-corrosion performance of the coating. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a graphene oxide loaded nanoparticle functionalized anti-corrosion coating. The filler prepared by the method solves the problem of graphene oxide agglomeration in the coating, introduces nanoparticles to optimize the coating structure, fills the micropores and microcracks inside the coating, enhances the density of the coating, reduces the defects in the coating, and improves the protective performance of the coating.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating comprises the following steps:

[0008] (1) Preparation of graphene oxide loaded nanoparticle composites:

[0009] 1) adding 0.4 g of nanoparticles to a mixed solution of ethanol and deionized water for ultrasonic dispersion, dropping an amino silane coupling agent, heating and stirring at 50-100° C. in a water bath for 4-9 hours, filtering, and vacuum drying to obtain surface amino nanoparticles;

[0010] 2) adding the surface-aminated nanoparticles and graphene oxide to an ethanol solution for ultrasonic dispersion, and dripping a carboxyl activator to promote an esterification reaction between the amino groups on the surface of the nanoparticles and the carboxyl groups on the surface of the graphene oxide;

[0011] 3) stirring the reaction in an oil bath at 50 to 130° C. for 3 to 10 hours, filtering the mixture, and vacuum drying the obtained solid powder to obtain a composite material of graphene oxide loaded nanoparticles as a filler;

[0012] (2) Preparation of anti-corrosion coating:

[0013] Weigh xylene, n-butanol and filler in proportion, sonicate, weigh the epoxy resin, continue sonicating and stirring, add defoamer, leveling agent, wetting dispersant and curing agent, stir evenly, let stand for 30 minutes and then spray on the substrate surface as an anti-corrosion coating.

[0014] Further description, in step 1), the aminated silane coupling agent is at least one of aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, aminoethylaminopropyltrimethoxysilane, aminoethylaminopropyltriethoxysilane, etc.

[0015] Further description, in step 1), the nanoparticles include at least one of titanium dioxide, zinc oxide, zinc sulfide, aluminum oxide, aluminum hydroxide, copper oxide, ferrosoferric oxide, silicon carbide, molybdenum disulfide, ferrous oxide, carbon nanotubes, zirconium dioxide, nickel oxide, tungsten oxide, manganese dioxide, chromium oxide, molybdenum oxide, calcium oxide, boron nitride, etc.; the mass ratio of the ethanol solution: deionized water: silane coupling agent is 5:2:4.

[0016] Further description, in step 2), the carboxyl activator is at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, calcium oxide, calcium chloride, barium chloride, triphenylphosphine, 1,3-dicyclohexylcarbodiimide, N,N-dicyclohexylcarbodiimide, imidazole, p-dimethylaminopyridine, aromatic thiophenol, etc.; the amount of the surface aminated nanoparticles is 0.4 g, the amount of graphene oxide is 0.1 g, and the carboxyl activator is 2 ml of a 2 mol / L solution.

[0017] It is further specified that in step (2), the mass ratio of xylene to n-butanol is 1:4.

[0018] It is further described that in step (2), the filler accounts for 0.3% to 1.5% of the epoxy resin by mass.

[0019] Further, in step (2), the defoaming agent is at least one of tributyl phosphate, trialkyl melamine, melamine cyanurate chloride, fatty amine, dialkyl phosphate, fluorinated alkyl phosphate, lauric acid, palmitic acid, polydimethylsilicone, etc.

[0020] Further, in step (2), the leveling agent is at least one of an organic silicon leveling agent, a polyether siloxane leveling agent, and an acrylate leveling agent, for example, at least one of an AKN-1033 leveling agent, a CM057 leveling agent, a BYK-349 leveling agent, and a KMT-7055 leveling agent.

[0021] Further, in step (2), the wetting and dispersing agent is at least one of a phosphate wetting and dispersing agent, an oily wetting and dispersing agent, and an ammonium polyacrylate dispersing agent, for example, at least one of LV-P2878 wetting and dispersing agent, KMT-7031 dispersing agent, and BYK-9076 dispersing agent.

[0022] Further, in step (2), the curing agent is an epoxy curing agent, for example, polyamide epoxy curing agent 5140.

[0023] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0024] (1) The preparation process of the composite filler prepared by the technical solution of the present application is relatively simple and does not require complex equipment or cumbersome steps. This simplification not only reduces production costs, but also improves production efficiency, making the technical solution of the present application have practical application value in industrial production. Incorporating the prepared composite filler into the coating system can significantly improve the agglomeration of graphene oxide and nanoparticles inside the coating. The nanoscale particles in these composite fillers can effectively fill the tiny holes inside the coating and form a synergistic effect with graphene oxide, which not only enhances the adhesion between the coating and the substrate, but also significantly improves the wear resistance, impact resistance and other properties of the coating, thereby improving the protective performance of the coating.

[0025] (2) Graphene oxide loaded with different types of nanoparticles can improve the performance of different aspects of the coating.

[0026] When graphene oxide is loaded with titanium dioxide as a coating filler, the UV resistance of the coating is significantly improved;

[0027] By loading silicon carbide with graphene oxide, the leveling and anti-corrosion properties of the coating are significantly improved, while its impact resistance is enhanced, making the coating tougher and more wear-resistant.

[0028] When graphene oxide is loaded with zinc oxide and zinc sulfide, the antibacterial and UV resistance of the coating are enhanced. In addition, zinc oxide can accelerate the reaction between epoxy and carboxyl groups and shorten the curing time.

[0029] The synergistic effect of these nanoparticles and graphene oxide enables the diversification of coating properties.

[0030] (3) After carboxyl activation, graphene oxide presents a three-dimensional wrinkled structure, which increases the contact area between the coating and the filler and enhances the toughness of the coating. The graphene oxide flakes play a good barrier effect in the coating and improve the anti-corrosion performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a process flow chart for preparing a functional anti-corrosion coating of graphene oxide loaded with nanoparticles of the anti-corrosion coating of the present invention.

[0032] Figure 2 The graph is a change in open circuit potential (OCP) of Example 2 of the present invention and Comparative Examples 1 to 3 when immersed in a 5.0% NaCl solution.

[0033] Figure 3 The SEM images of the anti-corrosion fillers of Comparative Example 3 (a) and Example 2 (b) of the present invention are shown.

[0034] Figure 4 This is the SEM image of the anti-corrosion filler prepared in Example 5 of the present invention.

[0035] Figure 5 The XRD diagrams of the fillers of Example 2 of the present invention and Comparative Example 3 are shown.

[0036] Figure 6 It is a comparison diagram of the Tafel curves of Example 2 of the present invention and Comparative Examples 1, 2, and 3.

[0037] Figure 7 These are neutral salt spray resistance test diagrams of Examples 2, 13, and 14 of the present invention and Comparative Examples 1, 2, and 3. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] Unless otherwise specified, the raw materials and reagents used in the examples are commercially available.

[0040] The graphene oxide used in the following examples was prepared by the Hummers method in this laboratory. Hummers method for preparing graphene oxide: flake graphite (1.0 g), NaNO 3 (1.0 g) and H 2 SO 4 (35 mL) were mixed in a beaker and stirred for 30 min in an ice bath. Then K 2 MnO 4 (4.0g), keep the temperature ≤15℃. Immediately transfer the beaker to a 30℃ oil bath and heat with stirring for 2h, slowly add 40mL of deionized water to avoid a sharp increase in the reaction temperature, and keep the temperature at 90℃ for 30min. Finally, centrifuge and filter, wash with 10% HCl aqueous solution to remove metal ions. Then, ultrasonically treat the dispersed GO solution for 30min to obtain the exfoliated GO.

[0041] Example 1

[0042] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0043] Molybdenum disulfide was added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and γ-aminopropylmethyldiethoxysilane was added dropwise and heated and stirred at 60°C in a water bath for 6 h to obtain surface amino-modified nano-silica (NH 2 -MoS 2 ). The mass ratio of the ethanol solution: deionized water: γ-aminopropylmethyldiethoxysilane is 5:2:4.

[0044] Take NH2 -MoS 2 After GO and GO were added to ethanol solution and ultrasonically dispersed for 1 h, 1-ethyl-(3-dimethylaminopropyl)carbodiimide was added dropwise to promote the formation of SiO 2 The surface amino groups and the carboxyl groups on the surface of GO undergo esterification reaction. The amount of the surface amino nanoparticles is 0.4 g, the amount of graphene oxide is 0.1 g, and the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 2 ml of 2 mol / L solution.

[0045] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0046] Preparation of anti-corrosion coating:

[0047] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add trialkyl melamine, AKN-1033 leveling agent, LV-P2878 wetting dispersant and polyamide epoxy curing agent 5140 dropwise, stir evenly and let stand for 30min before spraying on the substrate surface.

[0048] Example 2

[0049] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0050] Nano-silicon carbide was added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane was added dropwise and heated and stirred at 60°C in a water bath for 6 h to obtain surface amino-modified nano-silicon carbide (NH 2 -SiC). The mass ratio of the ethanol solution: deionized water: N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 5:2:4.

[0051] Take NH 2 -SiC and GO were added to an ethanol solution and ultrasonically dispersed for 1 hour, and then 1,3-dicyclohexylcarbodiimide was added dropwise to promote the esterification reaction between the amino groups on the surface of SiC and the carboxyl groups on the surface of GO. The amount of the surface amino-modified nanoparticles was 0.4 g, the amount of graphene oxide was 0.1 g, and the amount of 1,3-dicyclohexylcarbodiimide was 2 ml of a 2 mol / L solution.

[0052] The reaction was stirred in an oil bath at 60°C for 2 hours and then filtered. The obtained solid powder was vacuum dried at 80°C for 6 hours to obtain a SiC&GO composite material as a filler.

[0053] Preparation of anti-corrosion coating:

[0054] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add melamine cyanurate chloride, CM057 leveling agent, KMT-7031 dispersant and epoxy curing agent dropwise, stir evenly and let stand for 30min before spraying on the substrate surface.

[0055] Example 3

[0056] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0057] Nano-titanium dioxide was added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and aminopropyltrimethoxysilane was added dropwise and heated and stirred at 60°C in a water bath for 6 h to obtain surface amino-modified nano-titanium dioxide (NH 2 -TiO 2 ). The mass ratio of the ethanol solution: deionized water: aminopropyltrimethoxysilane is 5:2:4.

[0058] Take NH 2 -TiO 2 After adding GO to ethanol solution and ultrasonic dispersion for 1 h, N,N-dicyclohexylcarbodiimide was added dropwise to promote the 2 The surface amino groups and the carboxyl groups on the surface of GO undergo esterification reaction. The amount of the surface amino-treated nanoparticles is 0.4 g, the amount of graphene oxide is 0.1 g, and the amount of N,N-dicyclohexylcarbodiimide is 2 ml of a 2 mol / L solution.

[0059] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0060] Preparation of anti-corrosion coating:

[0061] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add polydimethylsilicone oil, BYK-349 leveling agent, BYK-9076 dispersant and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0062] Example 4

[0063] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0064] Nano-alumina and boron nitride were added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and 3-aminopropyltrimethoxysilane was added dropwise. The mixture was heated and stirred at 60°C in a water bath for 6 h to obtain surface amino-modified nano-alumina and boron nitride (NH2 -Al 2 O 3 -BN). The mass ratio of the ethanol solution: deionized water: 3-aminopropyltrimethoxysilane is 5:2:4.

[0065] Take NH 2 -Al 2 O 3 After BN and GO were added to ethanol solution and ultrasonically dispersed for 1 h, p-dimethylaminopyridine was added dropwise to promote Al 2 O 3 The amino groups on the surface of BN and the carboxyl groups on the surface of GO undergo esterification reaction. The amount of the surface-aminated nanoparticles used is 0.4 g, the amount of graphene oxide used is 0.1 g, and the amount of p-dimethylaminopyridine is 2 ml of a 2 mol / L solution.

[0066] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0067] Preparation of anti-corrosion coating:

[0068] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add polydimethylsilicone oil, KMT-7055 leveling agent, dialkyl phosphate and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0069] Example 5

[0070] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0071] Nano zinc oxide and zinc sulfide were added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and aminoethylaminopropyltriethoxysilane was added dropwise and heated and stirred at 60°C in a water bath for 6 h to obtain surface amino-modified nano zinc oxide and zinc sulfide (NH 2 -ZnO-ZnS). The mass ratio of the ethanol solution: deionized water: aminoethylaminopropyltriethoxysilane is 5:2:4.

[0072] Take NH 2 -ZnO-ZnS and GO were added to an ethanol solution and ultrasonically dispersed for 1 hour, and then triphenylphosphine was added dropwise to promote the esterification reaction between the amino groups on the surface of ZnO-ZnS and the carboxyl groups on the surface of GO. The amount of the surface amino-treated nanoparticles was 0.4 g, the amount of graphene oxide was 0.1 g, and the amount of triphenylphosphine was 2 ml of a 2 mol / L solution.

[0073] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0074] Preparation of anti-corrosion coating:

[0075] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add fatty amine, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0076] Example 6

[0077] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0078] Nano-alumina hydroxide, copper oxide and ferroferric oxide were added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and γ-aminopropyl triethoxysilane was added dropwise, and the mixture was heated and stirred at 60° C. in a water bath for 6 hours to obtain nano-amination-modified aluminum hydroxide, copper oxide and ferroferric oxide. The mass ratio of the ethanol solution: deionized water: γ-aminopropyl triethoxysilane was 5:2:4.

[0079] Take the surface aminated nano-hydroxy aluminum oxide, copper oxide, ferroferric oxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add calcium oxide to promote the esterification reaction between the amino groups on the surface of the hydroxy aluminum oxide, copper oxide and ferroferric oxide and the carboxyl groups on the surface of GO. The amount of the surface aminated nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the amount of calcium carboxylate is 2ml 2mol / L solution.

[0080] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0081] Preparation of anti-corrosion coating:

[0082] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonication for 20min, stir, add tributyl phosphate, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent dropwise, stir evenly and let stand for 30min before spraying on the substrate surface.

[0083] Example 7

[0084] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0085] Nano-molybdenum disulfide and ferrous oxide were added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and aminopropylmethyldimethoxysilane was added dropwise, and heated and stirred at 60° C. in a water bath for 6 hours to obtain surface-aminated nano-molybdenum disulfide and ferrous oxide. The mass ratio of the ethanol solution: deionized water: aminopropylmethyldimethoxysilane was 5:2:4.

[0086] Take the surface amino nano-molybdenum disulfide, ferrous oxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add calcium chloride to promote the esterification reaction between the amino groups on the surface of molybdenum disulfide and ferrous oxide and the carboxyl groups on the surface of GO. The amount of the surface amino nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the calcium chloride is 2ml 2mol / L solution.

[0087] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0088] Preparation of anti-corrosion coating:

[0089] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add dialkyl phosphate, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent dropwise, stir evenly and let stand for 30min before spraying on the substrate surface.

[0090] Example 8

[0091] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0092] Nano carbon nanotubes, zirconium dioxide and nickel oxide are added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and aminopropylmethyldimethoxysilane is added dropwise, and heated and stirred at 60° C. in a water bath for 6 hours to obtain surface amino-modified nano carbon nanotubes, zirconium dioxide and nickel oxide. The mass ratio of the ethanol solution: deionized water: aminopropylmethyldimethoxysilane is 5:2:4.

[0093] Take the surface amino-modified nano-carbon nanotubes, zirconium dioxide, nickel oxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add barium chloride dropwise to promote the esterification reaction between the amino groups on the surface of carbon nanotubes, zirconium dioxide and nickel oxide and the carboxyl groups on the surface of GO. The amount of the surface amino-modified nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the barium chloride is 2ml2mol / L solution.

[0094] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0095] Preparation of anti-corrosion coating:

[0096] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add fluorinated alkyl phosphate, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent dropwise, stir evenly and let stand for 30min before spraying on the substrate surface.

[0097] Example 9

[0098] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0099] Nano-tungsten oxide and manganese dioxide were added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and aminopropylmethyldiethoxysilane was added dropwise, heated and stirred at 60°C in a water bath for 6 hours to obtain surface-aminated nano-tungsten oxide and manganese dioxide. The mass ratio of the ethanol solution: deionized water: aminopropylmethyldiethoxysilane was 5:2:4.

[0100] Take the surface aminated nano-tungsten oxide, manganese dioxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add imidazole to promote the esterification reaction between the amino groups on the surface of tungsten oxide and manganese dioxide and the carboxyl groups on the surface of GO. The amount of the surface aminated nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the imidazole is 2ml 2mol / L solution.

[0101] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0102] Preparation of anti-corrosion coating:

[0103] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add lauric acid, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0104] Example 10

[0105] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0106] Nano-chromium oxide was added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane was added dropwise, and the mixture was heated and stirred at 60° C. in a water bath for 6 hours to obtain surface-aminated nano-chromium oxide. The mass ratio of the ethanol solution: deionized water: N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane was 5:2:4.

[0107] Take the surface aminated nano-chromium oxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add arylthiophenol to promote the esterification reaction between the amino groups on the surface of chromium oxide and the carboxyl groups on the surface of GO. The amount of the surface aminated nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the amount of arylthiophenol is 2ml 2mol / L solution.

[0108] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0109] Preparation of anti-corrosion coating:

[0110] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add palmitic acid, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0111] Embodiment 11

[0112] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0113] Nano-molybdenum oxide was added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane was added dropwise, and the mixture was heated and stirred at 60° C. in a water bath for 6 hours to obtain surface-aminated nano-molybdenum oxide. The mass ratio of the ethanol solution: deionized water: N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane was 5:2:4.

[0114] Take the surface amino nano-molybdenum oxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add arylthiophenol to promote the esterification reaction between the amino group on the surface of molybdenum oxide and the carboxyl group on the surface of GO. The amount of the surface amino nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the amount of arylthiophenol is 2ml 2mol / L solution.

[0115] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0116] Preparation of anti-corrosion coating:

[0117] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add palmitic acid, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0118] Example 12

[0119] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0120] Nano calcium oxide was added to a mixed solution of ethanol and deionized water for ultrasonic dispersion, and aminoethylaminopropyltrimethoxysilane was added dropwise, heated and stirred at 60°C in a water bath for 6 hours to obtain surface aminated nano calcium oxide. The mass ratio of the ethanol solution: deionized water: aminoethylaminopropyltrimethoxysilane was 5:2:4.

[0121] Take the surface aminated nano calcium oxide and GO and add them to the ethanol solution for ultrasonic dispersion for 1 hour, then add arylthiophenol to promote the esterification reaction between the amino groups on the surface of calcium oxide and the carboxyl groups on the surface of GO. The amount of the surface aminated nanoparticles is 0.4g, the amount of graphene oxide is 0.1g, and the amount of arylthiophenol is 2ml 2mol / L solution.

[0122] The mixture was stirred in an oil bath at 60° C. for 2 h and then filtered. The obtained solid powder was vacuum dried at 80° C. for 6 h to obtain a composite material as a filler.

[0123] Preparation of anti-corrosion coating:

[0124] Weigh 1.6g xylene, 0.4g n-butanol and 60mg filler, ultrasonicate for 20min, weigh 6g epoxy resin, continue ultrasonicate for 20min, stir, add palmitic acid, polyether siloxane leveling agent, dialkyl phosphate and epoxy curing agent, stir evenly and let stand for 30min before spraying on the substrate surface.

[0125] Embodiment 13

[0126] A method for preparing a graphene oxide loaded nanoparticle functionalized anti-corrosion coating, the preparation scheme is basically the same as that of Example 2, except that 18 mg of filler is added when preparing the anti-corrosion coating.

[0127] Embodiment 14

[0128] A method for preparing a graphene oxide loaded nanoparticle functionalized anti-corrosion coating, the preparation scheme is basically the same as that of Example 2, except that 90 mg of filler is added when preparing the anti-corrosion coating.

[0129] Comparative Example 1

[0130] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0131] This embodiment does not include the filler in Embodiment 2, and the remaining operations are the same as those in Embodiment 1.

[0132] Comparative Example 2

[0133] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0134] In this embodiment, the "SiC-GO" composite filler in Example 2 is replaced with a "GO filler", and the remaining operations are the same as those in Example 2.

[0135] Comparative Example 3

[0136] A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, comprising the following steps:

[0137] In this embodiment, the "SiC-GO" composite filler in Example 2 is replaced with a "SiC filler", and the remaining operations are the same as those in Example 2.

[0138] The multifunctional anti-corrosion coatings of graphene oxide loaded with nanoparticles prepared in Examples 1-12 and Comparative Examples 1-3 were tested as follows. The test results are shown in Table 1:

[0139] Table 1

[0140]

[0141]

[0142] After testing, in terms of coating adhesion strength and impact resistance, the adhesion strength of pure epoxy coating is the largest, but the impact resistance is weak; after adding fillers, the adhesion strength of epoxy resin decreases. Since the fillers in Comparative Examples 2 and 3 are unmodified graphene oxide and silicon carbide, and these two fillers are easy to agglomerate inside the coating, which leads to a decrease in the adhesion and impact resistance of the coating; Examples 1 to 14 are reduced graphene oxide loaded with nanoparticles after modification, which is more evenly dispersed inside the coating, so the adhesion strength decreases less. In addition, both nanoparticles and reduced graphene oxide have certain impact resistance, which can improve the impact resistance of the coating. In terms of coating hardness, since silicon carbide has the largest hardness, Example 2 and Comparative Example 3 have a larger hardness. In terms of corrosion resistance, the results of the neutral salt spray resistance test show that the corrosion resistance of the coating with graphene oxide loaded with nanoparticles as fillers is greatly increased, among which the anti-corrosion coating with graphene oxide loaded with silicon carbide as filler has the best corrosion resistance.

[0143] The above description is a detailed description of the preferred embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications completed under the technical concept suggested by the present invention should fall within the scope of the patent covered by the present invention.

Claims

1. A method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating, characterized in that: The following steps are involved: (1) Preparation of graphene oxide loaded nanoparticle composites: 1) adding 0.4 g of nanoparticles to a mixed solution of ethanol and deionized water for ultrasonic dispersion, dropping an amino silane coupling agent, heating and stirring at 50-100° C. in a water bath for 4-9 hours, filtering, and vacuum drying to obtain surface amino nanoparticles; 2) adding the surface-aminated nanoparticles and graphene oxide to an ethanol solution for ultrasonic dispersion, and dripping a carboxyl activator to promote an esterification reaction between the amino groups on the surface of the nanoparticles and the carboxyl groups on the surface of the graphene oxide; 3) stirring the reaction in an oil bath at 50 to 130° C. for 3 to 10 hours, filtering the mixture, and vacuum drying the obtained solid powder to obtain a composite material of graphene oxide loaded nanoparticles as a filler; (2) Preparation of anti-corrosion coating: Weigh xylene, n-butanol and filler in proportion, sonicate, weigh the epoxy resin, continue sonicating and stirring, add defoamer, leveling agent, wetting dispersant and curing agent, stir evenly, let stand for 30 minutes and then spray on the substrate surface as an anti-corrosion coating.

2. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step 1), the aminated silane coupling agent is at least one of aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, aminoethylaminopropyltrimethoxysilane, aminoethylaminopropyltriethoxysilane, etc.

3. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step 1), the nanoparticles include at least one of titanium dioxide, zinc oxide, zinc sulfide, aluminum oxide, aluminum hydroxide, copper oxide, ferrosoferric oxide, silicon carbide, molybdenum disulfide, ferrous oxide, carbon nanotubes, zirconium dioxide, nickel oxide, tungsten oxide, manganese dioxide, chromium oxide, molybdenum oxide, calcium oxide, boron nitride, etc.

4. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step 2), the carboxyl activator is at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, calcium oxide, calcium chloride, barium chloride, triphenylphosphine, 1,3-dicyclohexylcarbodiimide, N,N-dicyclohexylcarbodiimide, imidazole, p-dimethylaminopyridine, arylthiophenol, and the like.

5. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step (2), the mass ratio of xylene to n-butanol is 1:

4.

6. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step (2), the filler accounts for 0.3% to 1.5% of the epoxy resin by mass.

7. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step (2), the defoaming agent is at least one of tributyl phosphate, trialkyl melamine, melamine cyanurate chloride, fatty amine, dialkyl phosphate, fluorinated alkyl phosphate, lauric acid, palmitic acid, polydimethylsilicone, etc.

8. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step (2), the leveling agent is at least one of an organic silicone leveling agent, a polyether siloxane leveling agent, and an acrylate leveling agent.

9. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step (2), the wetting and dispersing agent is at least one of a phosphate wetting and dispersing agent, an oily wetting and dispersing agent, and an ammonium polyacrylate dispersant.

10. The method for preparing a graphene oxide-loaded nanoparticle functionalized anti-corrosion coating according to claim 1, characterized in that: In step (2), the curing agent is an epoxy curing agent.

Citation Information

Patent Citations

  • Composite nano-material reinforced solvent-type epoxy primer and preparation method thereof

    CN110791171A

  • Ferromanganese magnetic amino graphene oxide composite material as well as preparation method and application thereof

    CN111921512A

  • Preparation method of graphene oxide modified composite coating

    CN112552788A

  • Graphene-based polymer composite material, preparation method and application thereof

    CN113956700A

Cited By

  • Powder coating as well as preparation method and application thereof

    CN120310387A

  • Coating for high-performance light-weight carbon fiber and preparation method thereof

    CN121110376A

  • Multifunctional coating for plates and preparation method of multifunctional coating

    CN121801440A

  • A multifunctional coating for boards and its preparation method

    CN121801440B

  • Coating for galvanized sheet and preparation method thereof

    CN121801441A